Exploring visitors’ participation in museums and galleries using aesthetic visual markers - Ali, Susan Abubakir (2019)
Traditionally museums have been places that keep valuable artefacts and present them to visitors. However, in recent years and particularly in the developed countries, museums have shifted their focus beyond preserving and representing objects and content, towards a visitor-orientated approach to provide meaningful, unforgettable and interactive experiences. This has involved shifting the visitors’ role from passive consumers to active participants through involving them in different activities to engage them personally and emotionally with the exhibition, including consuming content, interacting with the exhibition and participating in designing their own content. To facilitate these activities, digital technologies in particular visual markers, usually in the form of QR codes, have been widely adopted in museums and galleries. They are relatively cheap, robust and easy to deploy as no new technical infrastructure needs to be installed; visitors use their own devices to scan the markers and retrieve multi-media contents and only new labels need to be added. Going further, QR codes can also be used to enable visitors to play games such as treasure hunts and even to contribute to the exhibitions by sharing own stories, interpretations, reflections and feedback. However, visitor engagement with QR codes in museum settings can often be low due to their inflexible and limited aesthetic quality, lack of meaning as the user cannot anticipate what kind of digital content can be revealed from scanning a QR code, as well as QR codes cannot be customised by users. Thus, this thesis explores the applications of a novel visual marker technology (Artcodes) which allows meaningful and aesthetic markers to be hand crafted in order to involve visitors in different types of participation in museums and galleries. Three practical studies were carried out in three different museum and gallery settings. The first study focused on exploring a novel interaction with exhibits by involving visitors physically manipulating visual representations of artefacts to reveal digital information about their relationships. To explore this interaction mechanism, an interactive paper map was developed on which visitors can place tangible artcode representations of artefacts and scan the resulting arrangements. Based on an in-situ study of its use, it was revealed that museum visitors engaged in different strategies for exploring the relationships between artefacts in the museum collection (inspection, strategic and experimental configuration), and for social collaboration (sharing the interaction space, adopting interaction roles and sharing a reaction to the “reveal”). The second study focused on exploring how visitors engage with labels which can be designed to be more aesthetic and meaningful, using artcodes, to augment exhibited photographic portraits in an art gallery with complimentary information in the form of audio recordings. The second focal point of the study was to explore artcodes as a mechanism for enabling visitors to contribute their own reflections to the exhibition by drawing a marker and linking it to an audio comment. Visitors’ hybrid contributions (artcodes) were then displayed within the exhibition space in order to find out how subsequent visitors engaged with them versus their interactions with the official markers. The findings show that visitors appreciated the use of the aesthetic markers and engaged with them at three levels – physical placement, aesthetic content and digital content. For content creation, the findings show that visitors appreciated engaging with the aesthetic visual markers to create meaningful contributions to express themselves through a combination of the physical image and the associated digital recording. The third study built on the second study to further explore how different visual representations of the markers (hand-drawn and pre-designed artcodes with/without comments section) can support visitors further to contribute to the exhibition and how subsequent visitors can interact with such contributions. Secondly, the study further explored how the artcodes approach can be adopted in practice by museum curators. The findings show that visitors appreciated being able to choose between different visual representations of artcodes for their contributions. They chose to draw artcodes for extending exhibition through sharing additional layer of contents about own experiences and stories. Whereas, the pre-designed artcodes were mostly chosen by the visitors to augment the existing objects through adding own comments about them. In addition, the findings show the important role that curators play in facilitating visitors’ contributions and integrating them into their setting. Building upon the findings from all 3 studies, the thesis concludes by proposing the co-creation cycle where visitors can participate, using aesthetic visual markers, in different types of activities through three different stages which are interaction, response and reintegration. The main opportunities and challenges for designers and museum practitioners are then outlined. This is followed by a set of guidelines for the practical implementation of the co-creation cycle in museums and galleries using aesthetic visual markers.